A fatal case of Rosai–Dorfman disease. Issue 8 (15th June 2017) - Bulyashki, Daniel; Brady, Zarina; Arif, Shahswar; Tsvetkov, Nikolay; Radev, Radoslav Stoyanov
Key Clinical Message: As Rosai–Dorfman Disease presents generally nonspecific symptoms, differential diagnosis can be of great learning curve for physicians. Additionally, RDD does not usually threaten life and spontaneous remission is frequently observed. However, unusually in our case the patient passed away within 1 month of confirmed diagnosis. Abstract : As Rosai–Dorfman Disease presents generally nonspecific symptoms, differential diagnosis can be of great learning curve for physicians. Additionally, RDD does not usually threaten life and spontaneous remission is frequently observed. However, unusually in our case the patient passed away within 1 month of confirmed diagnosis.